Modell för bedömning av underväxtens täthet - Persson, Johan (2017)
The purpose of this study was to develop and analyze a model for assessment of undergrowth density. The study was carried out on behalf of Stora Enso Skog. The developed model was quite simple: a plate the size of an A4-paper was placed on a stem in the forest stand. The plate was used to indirectly estimate the amount of undergrowth based on the percentage of the plate still visible from a set distance. By using predetermined limits, the model could serve as a decision tool for the forester during planning operations. In this study, however, no limits were defined. A survey was conducted among 30 respondents to check if the model was used differently by different individuals. The visible portion of the plate, expressed as a percentage, had a standard error of about 8.7 percent in this survey. Compared to the variation associated with estimations of other commonly used forestry parameters, such as basal area using relascope, this standard error is acceptable and proves that the model is interpreted in a similar way by different individuals. The visibility estimates also had an average standard deviation of about 13.4 and a range of variation around 53.5 percentage points. These values suggest that the model should be individually calibrated for each planner before use.